Defect of floor tiling / Muhammad Akram Hafiy Ahmad Sabri - Ahmad Sabri, Muhammad Akram Hafiy (Universiti Teknologi MARA, Perak, 2019)
Defect is one of the most common occurrences in any construction site, therefore this report will discuss in depth about the types of floor tile defect and how to determine it by follow the regulation that has been set. The aims for this report is to achieve the goal in solving the problem of floor tile defect by following the correct method. The objective of the report is to identify the general requirement of floor tiling. This is because the right installation method is depend upon the requirement that has been set. Furthermore, to determine the types of defect of floor tiling. This will make it easier to know why that problem occurred and how the way to fix it. This report has been carried out by means of observation while the supervisor is checking the defect and self repeated practices to proficient in determine it. To conclude, the tools and standard requirement of architectural work is very important to complete this report in order to check the floor tile defect with the right way by following the requirement.